2012
DOI: 10.1111/j.1541-1338.2011.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

From Identity Verification to Behavior Prediction: Ethical Implications of Second Generation Biometrics

Abstract: In this article, we will compare ethical issues raised by first and second generation biometrics. First generation biometrics use characteristics readily visible to the naked eye to ensure that the person identified is the person he claims to be, whereas second generation biometrics focus on behavioral patterns with the aim of predicting suspicious behavior or hostile intentions. While the collection of biometric features for identification is visible to the person involved, capturing biometric features from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Biometric systems can cause someone to be considered a criminal until evidence to the contrary is furnished. It is highly likely that this stigma will stick with such a person, for example, because the presumption is stored in a database (Sutrop and Laas-Mikko 2012;Sutrop 2010). This could be reinforced by facial recognition, which makes it easier to figure out a person's identity.…”
Section: Classification and The Presumption Of Innocencementioning
confidence: 99%
“…Biometric systems can cause someone to be considered a criminal until evidence to the contrary is furnished. It is highly likely that this stigma will stick with such a person, for example, because the presumption is stored in a database (Sutrop and Laas-Mikko 2012;Sutrop 2010). This could be reinforced by facial recognition, which makes it easier to figure out a person's identity.…”
Section: Classification and The Presumption Of Innocencementioning
confidence: 99%
“…This problem means that even highly reliable physiological authentication methods can easily be attacked when the network users are authenticated. Behavioral traits are called second-generation traits as compared to physiological traits, which are known as first-generation traits [387]. Using the current network approaches, user identity authentication is ineffective at protecting security in a network transaction environment; thus, researchers have attempted to verify user identity from the information exposed in their behavior data [388].…”
Section: B User Behavior Analysis Methodsmentioning
confidence: 99%
“…On ethical issues raised by second generation biometrics, a 2012 review by group of researchers 21 found similarities between ethical issues of both first generation biometrics (system that uses physical characteristics for identification) and second generation biometrics (system that uses behavioral patterns). The common ethical issues involve data integrity, privacy, and data protection.…”
Section: Biometric Ethical Issuesmentioning
confidence: 99%